Understandıng Counterfeıt Luxury Product Consumptıon: A Study Of Brand Conscıousness And Self-Congruence Among Yogyakarta Mıllennıals - Budi Setyanta; Mohamad Najmudin; Nurwiyanta Nurwiyanta; Aziz Prabowo (Asian Journal of Management, Entrepreneurship and Social Science, 2024)
Counterfeiting is a global problem that causes significant economic damage every year. Counterfeit products are made to look like genuine brands to deceive consumers, but they almost always have lower quality and fail to meet the safety standards required of authentic products. Some consumers buy these products unknowingly, while others intentionally purchase them. Indonesia loses IDR trillion due to the trade of counterfeit products. The study aimed to identify the intention to purchase counterfeit products among millennials in Yogyakarta. It considers consciousness and self-congruence as predictors of buying behavior. The study involved 100 respondents through online questionnaires using convenience sampling. Hypothesis testing was conducted using SEM-PLS to answer the research question, and gender was designed as a moderator. The results indicated that actual and functional self-congruence influences the intention to purchase counterfeit products. At the same time, brand and face consciousness do not significantly affect buying intention. The study also found that millennials' purchasing behavior of counterfeit products in Yogyakarta is not moderated by gender. However, further research is needed to examine the role of price perception and product characteristics due to the potential differences in consumer attitudes toward price and product characteristics